Childhood Predictors of Anxiety Symptoms: A Longitudinal Study - Grover, Rachel L. (2005)
The present study examined the concurrent and prospective relation between a select number of potential predictors and symptoms of anxiety among a high-risk community sample of 149 predominately African American children. Parent and child reports of anxiety were assessed in the first and seventh grade. Six domains of childhood risk factors (i.e., Loss-Death, Loss-Separation, Social Adversity, Negative Family Environment, Academic Difficulties, and Peer Rejection) were assessed using multiple informants in the first grade. Results indicated that children who experienced a more negative family environment, had a greater number of losses and deaths, and experienced academic failures in the first grade exhibited higher levels of anxiety (concurrently and/or at the six year follow-up). Findings provide empirical support to etiological models that posit both parental/familial and environmental factors contribute to the development of heightened anxiety in children.